Inhibition of redox/Fyn/c-Cbl pathway function by Cdc42 controls tumour initiation capacity and tamoxifen sensitivity in basal-like breast cancer cells - Chen, Hsing-Yu (WILEY-VCH Verlag, 2013)
We found that basal-like breast cancer (BLBC) cells use Cdc42 to inhibit function of the redox/Fyn/c-Cbl (RFC) pathway, which normally functions to convert small increases in oxidative status into enhanced degradation of c-Cbl target proteins. Restoration of RFC pathway function by genetic or pharmacological Cdc42 inhibition enabled harnessing of pro-oxidant effects of low µM tamoxifen (TMX) concentrations – concentrations utilized in trials on multiple tumour types – to suppress division and induce death of BLBC cells in vitro and to confer TMX sensitivity in vivo through oestrogen receptor-α-independent mechanisms. Cdc42 knockdown also inhibited generation of mammospheres in vitro and tumours in vivo, demonstrating the additional importance of this pathway in tumour initiating cell (TIC) function. These findings provide a new regulatory pathway that is subverted in cancer cells, a novel means of attacking TIC and non-TIC aspects of BLBCs, a lead molecule (ML141) that confers sensitivity to low µM TMX in vitro and in vivo and also appear to be novel in enhancing sensitivity to a non-canonical mode of action of an established therapeutic agent.